2014
DOI: 10.4028/www.scientific.net/amr.915-916.858
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Synthetic Skin: Materials Investigation, Experimentation and Simulation

Abstract: The skin, which acts as a protector of the body from potentially harmful external environment is a multi-layered tissue that exhibits complex mechanical behaviour. The aim of this paper is to review available studies of human skin using experimental and numerical methods in determining the mechanical properties of skin. Mechanical properties of skin are vital to the certain industries such as surgical, cosmetics, forensic science and etc., where skin study currently leads to the development of an ultimate skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Any further distribution of this work must maintain attribution to the author(s) and the title of the work, journal citation and DOI. nano-electronics [1,2], engineered artificial skin [3,4], microand nano-lithography [5,6] and soft sensors and actuators [7,8]. Quantitative nanomechanical characterization of soft materials [9][10][11][12][13] frequently plays an essential role in the design, development and further application of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Any further distribution of this work must maintain attribution to the author(s) and the title of the work, journal citation and DOI. nano-electronics [1,2], engineered artificial skin [3,4], microand nano-lithography [5,6] and soft sensors and actuators [7,8]. Quantitative nanomechanical characterization of soft materials [9][10][11][12][13] frequently plays an essential role in the design, development and further application of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is a lack of consensus on this issue since there have been studies with both positive and negative results . Moreover, it has been reported that many commercially available skin substitutes, listed later in this review, do not incorporate mechanical and textural similarity as they require mimicking of the biological and histological skin properties . Nonetheless, a study done by Nachman et al reported that the artificial skin model did illustrate the friction and deformation behavior of native skin.…”
Section: Introductionmentioning
confidence: 99%